Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Kinerja Keuangan: (Studi Empiris Perusahaan Sektor Pertambangan di BEI Tahun 2019-2023) - Ihsani, Nahda Thabita; Mulyani, Erly (Universitas Negeri Padang, 2026)
This study aims to prove and analyze the influence of green accounting and environmental performance on financial performance in mining sector companies on the Indonesia Stock Exchange. This study used 17 mining sector companies selected using the purposive sampling method. Data was adapted from the official IDX website and the website of each company selected as a sample. The study was conducted from 2019 to 2023. The data analysis method used was panel data regression, while hypothesis testing was carried out using the t-statistic test. Based on the results of the first hypothesis test, it was found that green accounting had a positive effect on financial performance, the results of the second hypothesis test also found that environmental performance had a positive and significant effect on the financial performance of mining sector companies on the Indonesia Stock Exchange from 2019 to 2023..